Strategic Approaches to Activating Academic Entrepreneurship in Modern Mega-Universities: Prospects for Ukraine - Novikova, I.E.; Zhylinska, O.I.; Osetskyi, V.L.; Bediukh, O.R. (Наука та інновації, 2020)
Introduction. Currently, R&D activity is the main in all the top universities in the world because it is focused on
the acquisition of new knowledge, while educational is only on the use of acquired knowledge. However, in Ukraine,
the trend of academic entrepreneurship development has not yet taken on proper significance.
Problem Statement. The implementation of the idea of intensifying the innovation-investment movement in
Ukrainian universities involves upgrading the existing innovation-oriented infrastructure and developing an
effective plan of action for those universities in which material and technical and intellectual foundation till have
a well-preserved.
Purpose. formulate strategic approaches to the commercialization of research products in modern mega-universities,
which generally involves the intensification of research activities in the context of international academic
entrepreneurship education as an imperative for the development of a high-tech, export-oriented and socially
responsible model of economy.
Materials and Methods. The methods of economic (in particular PEST- and SWOT-analyzes) and logicstructural
analysis, methods of comparison, synthesis, forecasting, theoretical generalization, as well as economicstatistical
methods of analysis of actual data are used.
Results. A result of this initiative is to formulate recommendations and steps to increase the non-budgetary
sources of funding for university research and innovation activities in Ukraine, in particular by raising the profitability
of intellectual property and the creation of small innovative enterprises.
Conclusions. The results obtained will allow us to formulate strategic principles in the development of a new
methodological paradigm for the commercialization of the results of intellectual work in universities, taking into
account
the development trends of the world and the features of national science. Вступ. Наразі науково-дослідна діяльність є провідною в найбільш рейтингових університетах світу, адже вона
орієнтована на отримання нових знань, тоді як освітню діяльність спрямовано безпосередньо на використання отриманих
знань. Проте в Україні розвиток академічного підприємництва не набув належного рівня.
Проблематика. Втілення ідеї активізації інноваційно-інвестиційного руху в університетах України передбачає
апгрейд наявної інноваційно-орієнтованої інфраструктури та розроблення реального плану дій для тих закладів, у
яких наявні матеріально-технічне та інтелектуальне підґрунтя.
Мета. Обґрунтувати стратегічні підходи до комерціалізації дослідницької продукції в сучасних мега-університетах,
що загалом передбачає активізацію провадження дослідницької діяльності у контексті просвітництва міжнародного
академічного підприємництва як імперативу розвитку високотехнологічної, експорторієнтованої та соціально-
відповідальної моделі економіки. Матеріали й методи. Використано методи економічного (зокрема PEST- і SWOT- аналізи) та логіко-структурного аналізу, методи порівняння, синтезу, прогнозування, теоретичного узагальнення, а також економіко-статистичні
методи аналізу фактичних даних. Результати. Сформульовано рекомендації та дієві кроки щодо примноження небюджетних джерел фінансування
університетської інноваційно-дослідницької діяльності в Україні, зокрема через підняття прибутковості об’єктів інтелектуальної
власності та створення малих інноваційних підприємств.
Висновки. Одержані результати дозволять сформувати стратегічні принципи розроблення нової методичної парадигми
комерціалізації результатів інтелектуальної праці в університетах з урахуванням тенденцій розвитку світової
та особливостей вітчизняної наук.